Genus Michaelus erraneously denominated as Thecla in Brazil - Pereira, Roberto Peixoto (Pesquisa Agropecuaria Brasileira, 2014)
In some insect surveys carried out on bean crops in the north region of the state of Rio de Janeiro, the occurrence of the pod borer Michaelus jebus (Godt., 1819) (Lepidoptera: Lycaenidae) was observed. However, in the Brazilian literature this insect is erroneously denominated as Thecla jebus, which is found only in the Palaearctic zone of the globe.